PENGARUH GAYA ARSITEKTUR BANGUNAN INDIS TERHADAP ASPEK SOSIAL DAN BUDAYA MASYARAKAT KABUPATEN BOYOLALI - Ibnu - Rustamaji (Universitas Sebelas Maret, 2019)
This research aims to find out the problems of the architectural Style of the Indis in Boyolali 1910 – 1915 who stay in city center and affected by the existence of the Boyolali village from socio-cultural. The problems related to this study are knowing the background of the history of Boyolali City, development of the architectural style of the building Indis, and social and cultural impact of the architectural style of the building Indis in boyolali. Based on the problem above, this research uses methods of historical research in the form of heuristics, source criticism, interpretation, and historiography. The results are that architecture of Indis have a major influence on the dynamics of Boyolali which tmeeting of two different cultures between European and indigenous cultures. Indis architectural style buildings in Boyolali can be seen in the city center in Pandanaran street Boyolali, and around Merapi and Merbabu street. Appearence architectural style Indis resulting cultural and social impact in the community. The impact of culture reflected in language, sciene and architecture. Social impact on the emergency of class and social status based on architectural style residence, Indis style and education.